A Comprehensive Study Of The Influence Of Attitudes, Actions And Nutritional Status On Risks Anemia In Adolescent Girls In Makassar - Imelda Iskandar; Nisma Nurkalisa; Azniah Syam (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2024)
Anemia is a health problem throughout the world, especially in developing countries, where it is estimated that 30% of the world's population suffers from anemia. Anemia occurs in many people, especially in young women. The physical symptoms of anemia in general are lethargy, weakness, tiredness, tiredness and inattention, frequent dizziness and dizziness in the eyes, someone who is anemic will even lose their appetite and have difficulty concentrating. The aim is to find out the relationship between attitudes, actions and nutritional status with the risk of anemia in young women at SMA Negeri 21 Makassar. This research uses quantitative research methods with a cross-sectional approach. This research was conducted at SMA Negeri 21 Makassar with a population of 486 and a sample of 83 respondents. Analysis used Chi-Square and Wilcoxon statistics with a significance level of α < 0.05. The statistical test results showed knowledge scores (p=0.725), attitude scores (p=0.553), action scores (p=0.014), nutritional status (p=0.000). The conclusion is that there is a relationship between actions, nutritional status and the risk of anemia and there is no relationship between knowledge, attitudes and the risk of anemia